2008
DOI: 10.1103/physrevb.78.144429
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism in gallium-dopedCeFe2: Martensitic scenario

Abstract: Ce͑Fe 1−x Ga x ͒ 2 compounds with x = 0, 0.01, 0.025, and 0.05 have been investigated to unravel the effect of Ga on the magnetic state of CeFe 2 . We find that the dynamic antiferromagnetic phase present in CeFe 2 gets stabilized with Ga substitution. The hysteresis loops show that while the compounds with x = 0 and 0.01 show normal ferromagnetic behavior, the other two show sharp multiple magnetization steps across the antiferromagnetic-ferromagnetic transition region. Temperature and time dependences of mag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
59
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 39 publications
12
59
1
Order By: Relevance
“…Nd 6 Co 1.67 Si 3 has T C =86 K and T * =39 K, in agreement with the values reported earlier [14]. It is noteworthy that though the impurity content was much less in this compound, the M-T behavior is almost identical to that of compound across the field induced antiferromagnetic to ferromagnetic phase transition [6,8,9]. However, unlike doped CeFe 2 , in the present case, there is a large remanence at low temperatures.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Nd 6 Co 1.67 Si 3 has T C =86 K and T * =39 K, in agreement with the values reported earlier [14]. It is noteworthy that though the impurity content was much less in this compound, the M-T behavior is almost identical to that of compound across the field induced antiferromagnetic to ferromagnetic phase transition [6,8,9]. However, unlike doped CeFe 2 , in the present case, there is a large remanence at low temperatures.…”
Section: Resultssupporting
confidence: 79%
“…It is to be noted that the step size and the location are the same in both the modes except in the 1 st loop. The step behavior and the hysteresis have been attributed to the characteristic features of the first order phase transition [8]. As mentioned earlier, usually the first order transitions…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have reported the magnetic properties of Ce(Fe 1-x Ga x ) 2 [15]. It was shown that in Ce(Fe 1-x Ga x ) 2 , the low temperature antiferromagnetic (AFM) state can be stabilized only for x≥0.025.…”
Section: Introductionmentioning
confidence: 99%